Embryo flash migration in fresh and frozen embryo transfers for day 3 and day 5 embryos. (July 2019) - Ozdemir, Ayse Z.; Ayas, Bulent; Guven, Davut; Turkmen, Aysın
Abstract: Objective: The aim of this study is to evaluate the embryo flash migration after 60 min from embryo transfer in fresh and frozen cycles. Design: 80 fresh and 81 frozen embryo transfers implemented Ondokuz Mayıs University between December 2017 and May 2018 were included in this prospective study. The fresh transfers performed at day 3 embryos as the frozen transfers were day 5 embryos. The distance between the embryo and the fundus was measured in the sagittal plane within 1 min of the transfer. After 60 min of bed rest the distance between the air bubble and the fundus was measured. The transfers were divided into three groups based on the migration of the embryos after the transfer. Embryos were classified as static if they were within 15 mm of their initial position. If they moved more than 15 mm towards the cervix or more than 15 mm towards the fundus, it was classified as cervical and fundal, respectively. Results: There was a statistically significant difference in embryo flash movements between frozen and fresh transfers (p < 0.05). In fresh transfers 48 patients (%60.0) were cervical, 14 patients (%17.5) were static and 18 patients (22.5%) were fundal. In frozen embryo transfers 31 patients (38.3%) were cervical, 31 patients (38.3%) were fundal and 19 (23.5%) patients were static. Conclusion: We found that cervical migration is lower in frozen transfers than in fresh transfers. This result may be related with the day of embryo or the endometrium in fresh or frozen cycles. Because in this study the embryos transferred were day 3 in fresh cycle and day 5 in frozen cycle. In frozen transfers there was not any significant difference in embryo position between pregnant and non-pregnant group. But in fresh transfers the cervical migration was significantly high in non-pregnant patients (p < 0.05).